Unveiling the CeO2 morphology effect in Pd-CeO2/C heterostructures catalysts for formic acid dehydrogenation. (15th August 2023) - Yuan, Zhongchun; Cao, Tingting; Deng, Min; Ma, Jun; Geng, Shuo; Yang, Chunliang; Ren, Yuan; Yao, Mengqin; Liu, Fei; Wang, Xiaodan
Graphical abstract: Highlights: Pd-sCeO2 /C has high performance in dehydrogenation of FA without additive. The properties of Pd-CeO2 heterostructure depend on the morphology of CeO2 . Synergy between crystal facets and defects is the key to obtain high reactivity. Construction of Pd-CeO2 heterojunction optimizes the chemical environment of Pd. Biomass carbon promotes heterojunction dispersion and introduces more defects. Abstract: It is very crucial but still a huge challenge to develop efficient and durable catalysts to promote hydrogen production from formic acid (FA). Herein, three CeO2 with structurally well-defined different shapes, i.e., sCeO2 (spheres), rCeO2 (rod) and oCeO2 (octahedral), are prepared, and their effect on the crystal faces and oxygen vacancy over the constructed heterostructure catalysts (Pd-CeO2 /C) have been intensively investigated in the FA dehydrogenation. Pd-sCeO2 /C outperforms the other catalysts with a turnover frequency (TOF) value of 2691 h −1 and selectivity to hydrogen of 100 % at 30 °C. A synergism between the CeO2 (1 1 0) facet and more oxygen vacancies is considered to be key to obtaining the high reactivity. Moreover, biomass carbon promotes the dispersion of Pd-CeO2 heterostructures due to its large specific surface area and causes more defects in the Pd-CeO2 /C. Combined with in-situ FTIR and density functional theory (DFT), it is speculated that FA is decomposed through formate pathway over the Pd-sCeO2 /C. This work thus provides a reasonable design and controllable synthesis strategy for the effective application of FA as an available liquid phase hydrogen storage material.